Pengaruh Assesmen Portofolio Berbasis E-Learning Dan Minat Baca Terhadap Kemampuan Berpikir Kritis Mahasiswa PGPAUD FIP UNM - Parwoto Parwoto; Rusmayadi Rusmayadi; Muh. Yusri Bachtiar (Seminar Nasional LP2M UNM, 2019)
The development of critical thinking skills is the main key objective besides developing reading interest and applying portfolio assessment in e-learning systems. The purpose of this study was to determine the effect of applying e-learning based portfolio assessments and reading interest on students' critical thinking skills. This type of research is a two-way ANOVA experiment with PGPAUD student subjects in the educational subjects of children with special needs. The results showed that there was a very significant difference in influence where students' critical thinking skills with the application of e-learning based portfolio assessments were better than the non-e-learning assignment based portfolio assessment methods. The critical thinking ability of students who have high reading interest is no higher than the critical thinking ability of students who have low reading interest. Recommendations for portfolio assessment based on e-learning and interest in reading are always developed in the learning system in universities to improve students' critical thinking skills